Preliminary study on Zeqi: from pharmacological action of active ingredients to clinical application research - Yanqi Liang; Xi Wang; Qing Sun; Rongling Wang; Xin Liu; Xuan Han (Acta Materia Medica)
Zeqi ( Euphorbia helioscopia L. ), is a widely distributed plant of the Euphorbiaceae family. Zeqi is a famous Chinese herbal medicine with the effects of inducing diuresis for removing edema, killing pathogens and relieve itching, etc. It can be used to treat edema, dysentery, osteomyelitis, cancer and many other diseases. With the development of processing and extraction technologies, a series of active substances have been extracted from Zeqi, including terpenes, steroids, tannins and flavonoids. Among these components, terpenes are the most abundant. Recent pharmacological studies indicated that Zeqi has multifunction including antitumor activity, antiviral activity, anti-inflammatory activity, anthelmintic activity, antibacterial activity, and antioxidant activity. To provide a more comprehensive analysis of the application of traditional Chinese medicine Zeqi in clinical treatment and modern medicine, we summarize in this review the pharmacological studies on Zeqi in recent years.